Strategi Siaran LPP RRI Jayapura dalam Meningkatkan Minat Pendengar Masyarakat Kota Jayapura - Masni Sanmas; Nurjayanti Nurjayanti; Muhammad Yusron (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2024)
The rapid development of information and communication technology today has provided space for people to get information easily and quickly. Information media continues to change along with the development of the era that demands everything is digital. This is a challenge for the world of broadcasting, especially radio, to continue to maintain its existence. The purpose of this research is to find out how the strategy carried out by LPP RRI Jayapura in increasing the interest of listeners in the city of Jayapura. The object of this research is LPP RRI Jayapura. The research method used is a qualitative descriptive approach by determining informants by purposive sampling. Data collection is obtained through observation, interviews, and documentation. The results of this study show that in increasing listener interest, LPP RRI Jayapura carries out various strategies including: First, In terms of radio broadcast programs, it can be grouped into four stages, namely: a), program planning includes: program ideas, target listeners, broadcasting time, production costs, to organizing work teams. b), program production, program production carried out by LPP RRI Jayapura, namely creating an event program that is suitable for each daypart by meeting the targets in each program. c), program execution, for the leading executor in this case, namely an announcer so that the selection of LPP RRI Jayapura broadcasters adjusts to the character of each program. d), program supervision and evaluation, for supervision in the broadcast process will be accounted for by the head of each program, but in the organizational structure the heads of fields will account to the head of the station, in general supervision and evaluation will be carried out by SPI (Internal Supervisory Rules) RRI every three months. Second, RRI Digital broadcast radio Jayapura. The management of digital-based broadcast radio is distributing radio broadcasts on online media such as facebook, youtube, RRIPlay Go application, streaming radio and RRINET. Key words: Broadcast Strategy, LPP RRI Jayapura, Listener Interest